2005
DOI: 10.1111/j.1469-8986.2005.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Parametric exploration of the fear‐inhibited light reflex

Abstract: The effect of various parameters on the mediation of the fear-inhibited light reflex was examined. The light reflexes of 16 healthy men were measured across four light probe intensities, either in the presence of white noise alone or when the white noise was associated with the threat of either an electric shock or an acoustic sound blast. The white noise alone did not affect the light reflex amplitude. Both types of threat were subjectively anxiogenic and inhibited the light reflex across all light probe inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
1
8
0
1
Order By: Relevance
“…Furthermore, they report that subjects' pupil size mirrored these effects, demonstrating contagion such that subjects' pupils constricted in response to the viewing small-pupil faces. Although we did not measure such changes in the present study, 1 critical caveat to consider is that direct stimulation of the amygdala is consistently associated with pupil dilation rather than constriction ( Ursin and Kaada 1960 ; Koss and Wang 1972 ; Loewy et al 1973 ; Saper et al 1976 ; Cedarbaum and Aghajanian 1978 ; Applegate et al 1983 ; Breen et al 1983 ; Koss et al 1984 ; Kapp et al 1994 ; Holstege 1987 ; Bitsios et al 1996 ; Bitsios et al 1998 , 1999 ; Gloor 1997 ; Hourdaki et al 2005 ). Thus, it is somewhat unclear under what circumstances BOLD signal activation in the amygdala might index pupil constriction.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, they report that subjects' pupil size mirrored these effects, demonstrating contagion such that subjects' pupils constricted in response to the viewing small-pupil faces. Although we did not measure such changes in the present study, 1 critical caveat to consider is that direct stimulation of the amygdala is consistently associated with pupil dilation rather than constriction ( Ursin and Kaada 1960 ; Koss and Wang 1972 ; Loewy et al 1973 ; Saper et al 1976 ; Cedarbaum and Aghajanian 1978 ; Applegate et al 1983 ; Breen et al 1983 ; Koss et al 1984 ; Kapp et al 1994 ; Holstege 1987 ; Bitsios et al 1996 ; Bitsios et al 1998 , 1999 ; Gloor 1997 ; Hourdaki et al 2005 ). Thus, it is somewhat unclear under what circumstances BOLD signal activation in the amygdala might index pupil constriction.…”
Section: Discussionmentioning
confidence: 85%
“…By contrast, the parasympathetic nerve fibers responsible for pupil constriction arise from the Edinger–Westphal nucleus within the brain stem and innervate the circular muscles of the iris. Although it is anatomically plausible then that the amygdala facilitates pupil dilation by either stimulating sympathetic inputs or inhibiting parasympathetic inputs, research to date suggests that the amygdala's effect on dilation is likely an inhibition of parasympathetic input ( Bitsios et al 1996 , 1998 , 1999 ; Hourdaki et al 2005 ). The existing data further suggest that the amygdala influences pupil dilation through an indirect route via the hypothalamus ( Koss and Wang 1972 ; Saper et al 1976 ; Holstege 1987 ) and/or locus coeruleus ( Loewy et al 1973 ; Breen et al 1983 ; Koss et al 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous neuroimaging study showed that at least Intransitive inner gestures (usually performed toward the body) activate brain regions associated to theory of mind 16 that included the bilateral amygdala. The amygdala is described to play a role in pupil dilation by stimulating the sympathetic input or by inhibiting the parasympathetic one 21,22,36,37 . Hence, since Intransitive gestures are particularly sensitive to elicit the activity of the amygdala, pupil dilation might be interpreted as a consequence of the activity of the amygdala on the sympathetic or parasympathetic system.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of this triggered auditory pupil response may therefore reflect the state of arousal at the time of probing, resulting in discrimination between CS+, CS−, and intertrial interval probes. Other pupillary reflexes, triggered during US anticipation, have previously served as measures of conditioned fear: it has been demonstrated that the pupil constriction in response to light flashes is inhibited during threat anticipation (Bitsios, Szabadi, & Bradshaw, ; Hourdaki et al, ). This inhibition of the pupillary light reflex was also found to follow emotional arousal rather than valence (Bitsios, Szabadi, & Bradshaw, ; Henderson, Bradley, & Lang, ) and to rely on different circuitry than the acoustic startle reflex (by being susceptible to different pharmacological manipulations; see Bitsios, Philpott, Langley, Bradshaw, & Szabadi, ).…”
Section: Discussionmentioning
confidence: 99%